SINTESIS METIL ESTER DARI LIMBAH KELAPA SAWIT DENGAN SONOCHEMISTRY DAN CRACKING MENJADI BIOFUEL DENGAN KATALIS CrMo/HZ - Jertadi Putri Dhani; Agus Sundaryono; Dewi Handayani (ALOTROP, 2019)
This study aims to calculate the percentage methyl ester converted to biofuel through catalytic cracking reaction,analyzes component and determine characteristics using catalyst CrMo/HZ. This research begins with impregnation sample preparation which includes heating oil,degumming,bleaching and determination free fatty acid (FFA). Methyl ester obtained from liquid waste conversion crude palm oil through an esterification and transesterification reaction with H2SO4 and NaOH catalyst with sonochemistry methode is a method that utilizes ultrasonic waves origanating from a device is ultrasonic cleaner for one hour at temperature 60oC. The methyl ester obtained was cracked with a CrMo/HZ catalyst which was carried out for 2 hours at temperatur 380oC. To find out the components of compounds formed in methyl ester, an analysis was performed using GCMS then characteristics of biofuel are determined from the result of catalytic cracking obtained through acid number testing,density,viscosity,pour point and fog point. The result obtained from the conversion of methyl ester to biofuel with Crmo/HZ Catalyst Is 60,17% And For Testing The Physical Characteristics Of Biofuel Namely The Acid Number 1,87 Mg KOH/G, density 0,804 g/cm3, viscosity 1,162 Cst, pour point 0oC and fog point 1,4oC. The result of cracking produce a consituent component of biofuel namely gasoline 33,67%, kerosene 16,26%, gas oil 10,24% beside that, there are still methyl ester as much as21,89%.